The friends we keep [large type] - Green, Jane, 1968- (Thorndike Press large print core, 2019)
Evvie, Maggie, and Topher have known each other since university. Their friendship was something they swore would last forever. Now years have passed, the friends have drifted apart, and none of them ever found the lives they wanted - the lives they dreamed of when they were young and everything seemed possible. Evvie starved herself to become a supermodel but derailed her career by sleeping with a married man. Maggie married Ben, the boy she fell in love with at university, never imagining the heartbreak his drinking would cause. Topher became a successful actor but the shame of a childhood secret shut him off from real intimacy. By their thirtieth reunion, these old friends have lost touch with each other and with the people they dreamed of becoming. Together again, they have a second chance at happiness... until a dark secret is revealed that changes everything. The Friends We Keep is about how despite disappointments we've had or mistakes we've made, it's never too late to find a place to call home.